Crisis of the principle of legality: recurring but necessary discussion in Latin America - Aponte Arcila, Jonás Eduardo (2022)
The purpose of this article is to analyze the causes of a possible crisis of the principle of legality, from a theoretical perspective. Certain factors related to the denial of the law as protector of freedom and limiter of political power would be in the origin of this crisis. Constituent processes, the establishment of a social State in a formal sense and the delegation of enabling laws caused the law to lose its place in a State governed by the rule of law. This study presents a brief but meticulous documentary compilation of literature that deals with this problem, special emphasis has had the contributions of Laporta, Hayek and Nieto. The latter has often denied the existence of the principle of legality. It is concluded that power will always seek to disregard legality and, therefore, individual freedoms are not duly protected. Finally, the article seeks to feed this discussion further and enhance its relevance to build solid democratic pillars.